Aliyatu Al-Tamasuki Al-Nashyi fi Al-Qurani Al-Karimi Wa Dalalutuha fi Tafsiri Al-Kassyafi - Osamah Saleh Mohammed Allbail; Rijal Mahdi (Departement of Arabic Language and Literature, IAIN Syekh Nurjati Cirebon, 2020)
This research aims to highlight the importance of context and its role in the coherence of the text and describe the coherence mechanisms revealed by Al-Zamakhshari during his interpretations. Al-Zamakhshari is considered one of the first who follow this aspect. The context is in its fate, giving it multiple meanings or limiting it to one meaning, and among the mechanisms mentioned by Al-Zamakhshari is the referral listing types and indicating its importance. The mechanisms are repetition and sympathy, and all of this will become clear during the research. The research followed a descriptive approach, but it did not remain a captive to it, but tried to benefit from other approaches as much as possible. The research has drawn conclusions from them; First: Although al-Zamakhshari mention the word context only a few times, he used it a lot during his interpretation, as he deal with most contextual phenomena in an approach that reveals Zamakhshari's awareness of the importance of context in understanding the meaning. Second: Al-Zamakhshari realized the importance of text cohesion, and what repetition and referral bring about linking the text to each other. He took care of the assignee and the multiplicity of the assignee, which leads to the coherence of the text, this does not mean that he left it unchecked or restricted as he stresses the importance of taking into account the internal context and taking into account the Qur’anic systems. And its linguistic function, and its usefulness for the addresses, as Zamakhshari believes that repetition is rhetorical unless it benefits the reader, or the speaker wants to deliver a message to the reader through him. Third: Al-Zamakhshari paid great attention to conjunctions, and al-Zamakhshari showed the ability of conjunctions to connect parts of the text. يهدف هذا البحث إلى إبراز أهمية السياق ودوره في ترابط النص وتناسقه ووصف آليات التماسك التي كشف عنها الزمخشري أثناء تفسيره، ويعد الزمخشري من السباقين إلى تتبع هذا الجانب، فقد أولى هذا التماسك عناية فائقة، إذ ذهب إلى إبراز روابط النص، ودلالة هذه الروابط ومدى تأثير السياق في مآلاتها، وإعطائها معانٍ متعددة أو قصرها على معنى واحد، ومن الآليات التي ذكرها الزمخشري الإحالة معددا أنواعها ومبينا أهميتها ومن الآليات التكرار والعطف وسيتضح كل ذلك أثناء البحث. وقد اتبع البحث منهجا وصفيا، ولكنه لم يبق أسيرًا له، بل حاول الإفادة من المناهج الآخرى قدر الإمكان. لقد توصل البحث إلى نتائج منها؛ أولا: على الرغم من أن الزمخشري لم يذكر لفظ السياق إلا بضع مرات، إلا أنه استخدمه كثيرًا أثناء تفسيره، فقد تناول معظم الظواهر السياقية تناولًا يكشف عن إدراك الزمخشري لأهمية السياق في فهم المعنى. ثانيا: أدرك الزمخشري أهمية تماسك النص، وما يحدثه التكرار والإحالة من ربط النص بعضه ببعض. وقد اعتنى بالمحال والمحال إليه وبتعدد المحال إليه، والذي يؤدي إلى ترابط النص، فهذا لا يعني أنه قد تركه دون ضابط أو قيد إذ يشدد على أهمية مراعاة السياق الداخلي، ومراعاة النظم القرآني، ولكن الباحث لاحظ أن الزمخشري حينما تناول ظاهرة التكرار تناوله من جانب المعنى، ووظيفته اللغوية، وفائدته بالنسبة للمخاطب، إذ يرى الزمخشري أن التكرار يعد لغوًا إلا إذا أفاد فائدة للقارئ، أو أراد المتكلم إيصال رسالة للقارئ من خلاله. ثالثا: اهتم الزمخشري اهتمامًا كبيرًا بالعطف، وبين الزمخشري قدرة العطف على ربط أجزاء النص، ولم يكتف بذلك بل إنه كان يحدد دلالة حروف العطف وأسباب اختيارها.